Development of an Inclusive Religious Literacy Model in Local Churches in Maluku and North Maluku - Rouli Retta Trifena Sinaga; Johan Robert Saimima (Sekolah Tinggi Teologi Intheos Surakarta, 2026)
The memory of the interfaith conflicts in Maluku and North Maluku from 1999 to 2004 reproduced to give rise to the current conflict is crucial to be noticed. The purpose of this study is to explain an inclusive religious literacy model in local churches by mapping the social and cultural capital at the local churches’ level, then analyzing empirical data on inclusive religious literacy in the local churches and developing an inclusive religious literacy model in the local churches in Maluku and North Maluku. By using qualitative method a phenomenological approach to inclusive religious literacy based on Pancasila and Joseph Cardinal Ratzinger’s concept of the meaning of Christian brotherhood that is in dialogue with social and cultural capital in the local churches’ context, especially in Maluku and North Maluku, besides the local churches’ teachings, regulations, and programs, is carried out in this research. The finding of this research is that the Protestant Church of Maluku in the synodal, clasis, and congregational levels has implemented inclusive religious literacy in Maluku and North Maluku and it is developed from this research as an inclusive religious literacy model based on the local wisdoms of fraternity of the contexts.